MILLENNIAL MOTIVATION IN MAXIMIZING P2P LENDING IN SMEs FINANCING - Lia Febria Lina; Dhiona Ayu Nani; Dian Novita (Politeknik Negeri Batam, 2021)
Fintech is known as one of the most important innovations unity in financial industry that is growing rapidly and increase financial inclusion, especially the expansion of access to capital for SMEs. However, research related to this is still limited. This research tries to extend TAM model in financial context by adding external variables such as financial knowledge and financial risk tolerance as driving factor millennials to invest in Fintech P2P lending. This research uses quantitative research using primary data and uses Partial Least Squares-Structural Equation Modelling (PLS- SEM) to analysis the data that has been collected. The result indicates that millennial investment intentions are influenced by perceived usefulness, and risk averse. Findings in this research proves that the users who tend to avoid risks and uncertainties can be encouraged to invest in P2P lending. In the term of technology factor, users who believe that the features in the application of P2P lending is useful and beneficial will encourage users to invest.